Interaction effects and superconductivity signatures in twisted double-bilayer WSe2. Issue 9 (22nd July 2020) - An, Liheng; Cai, Xiangbin; Pei, Ding; Huang, Meizhen; Wu, Zefei; Zhou, Zishu; Lin, Jiangxiazi; Ying, Zhehan; Ye, Ziqing; Feng, Xuemeng; Gao, Ruiyan; Cacho, Cephise; et al.
Abstract : Twisted bilayer graphene provides a new two-dimensional platform for studying electron interaction phenomena and flat band properties such as correlated insulator transition, superconductivity and ferromagnetism at certain magic angles. Abstract : Twisted bilayer graphene provides a new two-dimensional platform for studying electron interaction phenomena and flat band properties such as correlated insulator transition, superconductivity and ferromagnetism at certain magic angles. Here, we present experimental characterization of interaction effects and superconductivity signatures in p-type twisted double-bilayer WSe2 . Enhanced interlayer interactions are observed when the twist angle decreases to a few degrees as reflected by the high-order satellites in the electron diffraction patterns taken from the reconstructed domains from a conventional moiré superlattice. In contrast to twisted bilayer graphene, there is no specific magic angle for twisted WSe2 . Flat band properties are observable at twist angles ranging from 1 to 4 degrees. Our work has facilitated future study in the area of flat band related properties in twisted transition metal dichalcogenide layered structures.